2020
DOI: 10.1002/bab.2047
|View full text |Cite
|
Sign up to set email alerts
|

Circulating mRNA and plasma levels of osteoprotegerin and receptor activator of NF‐κB ligand in nonalcoholic fatty liver disease

Abstract: Pathogenesis of the beginning and progression of nonalcoholic fatty liver disease (NAFLD) has not been clarified exactly. The osteoprotegerin (OPG)/receptor activator of NF-κB ligand (RANKL) axis seems to play an imperative function in the onset and progression of this disease. The goal of the present study was to investigate the peripheral blood mononuclear cell (PBMC) expression and plasma levels of RANKL and OPG cytokines in NAFLD patients and compare them with healthy group. Plasma levels of OPG and RANKL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In the present study, we found that the hepatocyte OPG level was significantly decreased in patients with NASH, NASH animal models, and cellular models. Most clinical studies have shown decreased circulating-OPG levels in patients with NASH 12,16,17 ; however, one study has reported increased OPG levels 18 . These differences may be attributed to factors including ethnicity, different diagnostic criteria, and different manufacturers of test kits.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that the hepatocyte OPG level was significantly decreased in patients with NASH, NASH animal models, and cellular models. Most clinical studies have shown decreased circulating-OPG levels in patients with NASH 12,16,17 ; however, one study has reported increased OPG levels 18 . These differences may be attributed to factors including ethnicity, different diagnostic criteria, and different manufacturers of test kits.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α and IL-6 jointly promote the formation of osteoclasts and increase bone resorption [17] . In diet-induced NAFLD rodents, RANKL is upregulated both in circulation and liver [18] , and blocking RANKL signaling in liver can improve liver insulin resistance in HFD mice, suggesting that RANKL plays an important role in the pathogenesis of NAFLD [19] . In bone, RANKL binds to RANK on the surface of osteoclast precursors to promote osteoclast generation and bone resorption, while OPG, as a trick receptor, can inhibit the intercellular merger of RANKL and RANK, resulting in reduced activity, proliferation and survival of osteoclasts [20] .Our results show that TNF-α and IL-6 can affect osteoclast function and lead to osteoporosis by regulating the biological activity of the OPG/RANK/RANKL triplet [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Runx2 is speci cally elevated in liver stellate cells (mHSC) of NAFLD mice, and accelerates the evolution of NAFLD to NASH by inducing macrophage migration in vitro [19] . Meanwhile, Runx2 plays a decisive role in the osteoblastic differentiation of bone marrow mesenchymal stem cells [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, its lower levels may indicate thymic involution and a decrease in naive T‐cells. TRANCE/RANKL plasma levels have also been reported lower in patients with nonalcoholic fatty liver disease (Nikseresht et al, 2020 ), a condition related to insulin resistance and obesity. TRANCE/RANKL has been shown to suppress proinflammatory cytokine production in mouse model (Maruyama et al, 2006 ); however, in humans, the RANKL gene mutations do not result in an increased risk of immune disorders and its inhibitor (denosumab) has no significant effect on inflammatory processes (Ferrari‐Lacraz & Ferrari, 2011 ).…”
Section: Discussionmentioning
confidence: 99%